Assessing Academic Success and Its Predictors from the Perspective of Nursing Students in Kashan University of Medical Sciences - Mohsen Adib-Hajbaghery; hamidreza sadeghi gandomani; Efat Aminolroayaee Yamini (مجله ایرانی آموزش در علوم پزشکی, 2015)
Introduction: Identifying the factors influencing nursing students’ academic success is of great importance. Due to controversies on the role of influencing factors, this study aimed to identify the predictors of academic success among nursing students of Kashan University of Medical Sciences. Methods: In this cross-sectional study, 134 sophomore to senior nursing students studying at Kashan University of Medical Sciences were selected through systematic random sampling in 2014. The data was collected through a questionnaire including demographic and academic success information which was used after confirming its validity and reliability. Data were analyzed using Chi-square, Kruskal-Wallis, Mann-Whitney and Spearman correlation coefficient. Results: Non-native status and staying in dormitory had positive effects on academic success (p < 0.05). No significant difference was observed between the students’ academic success mean scores in different semesters despite an increase in academic success of students in final semesters (p=0.26). The overall mean score of academic success was 105.23±10.02 out of the highest possible score of 156 (67.30% out of the overall score). No significant correlation was observed between the students’ overall GPA and the last term GPA with academic success score (p = 0.59). Conclusion: Considering the predicting role of demographic factors in the nursing students’ academic success; the authorities should plan to improve the students’ academic success.